2019
DOI: 10.1002/smll.201903809
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide Nanosheet/Quantum Dot Dynamic Memristive Structure Driven by Photoinduced Phase Transition

Abstract: MoS2 2D nanosheets (NS) with intercalated 0D quantum dots (QDs) represent promising structures for creating low‐dimensional (LD) resistive memory devices. Nonvolatile memristors based 2D materials demonstrate low power consumption and ultrahigh density. Here, the observation of a photoinduced phase transition in the 2D NS/0D QDs MoS2 structure providing dynamic resistive memory is reported. The resistive switching of the MoS2 NS/QD structure is observed in an electric field and can be controlled through local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…The emergence of graphene has aroused universal interest in 2D materials with unique properties and fascinating functionalities, enabling their great progress of applications in a wide range of area such as electronics, energy, sensors, physics and biomedicines, etc. [ 1–32 ] 2D materials can not only be isolated and thinned into single atomic thickness, and stack vertically or laterally forming heterostructures through van der Waals (vdWs) forces, but also can be modified their electrical, optical, catalytic, and magnetic properties by doping and functionalization strategies like other nanomaterials. [ 33–40 ] In analog to graphene, the most related class of 2D materials is the emerging monoelemental 2D materials named Xenes, which borrow the etymology from similar sp 2 hybridized bonds and the honeycomb‐like atomic structure.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of graphene has aroused universal interest in 2D materials with unique properties and fascinating functionalities, enabling their great progress of applications in a wide range of area such as electronics, energy, sensors, physics and biomedicines, etc. [ 1–32 ] 2D materials can not only be isolated and thinned into single atomic thickness, and stack vertically or laterally forming heterostructures through van der Waals (vdWs) forces, but also can be modified their electrical, optical, catalytic, and magnetic properties by doping and functionalization strategies like other nanomaterials. [ 33–40 ] In analog to graphene, the most related class of 2D materials is the emerging monoelemental 2D materials named Xenes, which borrow the etymology from similar sp 2 hybridized bonds and the honeycomb‐like atomic structure.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MoS 2 shows semiconducting properties in the 2H phase with a triangular prism structure and becomes metallic when it is transformed into a 1T (1T′) phase with a twisted octahedral structure. [ 26,70 ] The MoS 2 memristors have been developed by local 2H‐1T′ phase transitions via applying the electric field, [ 71 ] controlling the migration of Li + ions with an electric field, [ 26 ] or photo‐irradiation [ 72 ] . A MoTe 2 memristor is also explored by electrically driven 2H to 1T′ phase transformation.…”
Section: Artificial Neural Systemsmentioning
confidence: 99%
“…It has previously been reported that the 2D crystals can be transformed from metallic to semiconducting phases via photoinduction with subpicosecond dynamics [169]. Fu et al demonstrated a reversible 2H-1T phase transition of a MoS 2 nanosheet/QD (2D/0D) structure controlled by photoexcitation of the QDs, and used the transition as a dynamic photoresistive memory device [170]. The QD and nanosheet dispersion was deposition between two graphene electrodes on a SiO 2 /Si chip.…”
Section: Resistive Switching/memory Devicesmentioning
confidence: 99%